STRATEGIC MANAGEMENT AND THE USE OF INFORMATION AND COMMUNICATION TECHNOLOGIES BY SELECTED SOUTH AFRICAN AND AMERICAN STUDENTS - HOUGH, JOHAN; NEULAND, ERNST (South African Journal of Higher Education, 2016)
This research focuses on the value of Strategy Teaching and the impact of current information, communication, technologies (ICT) on the business life of students in South Africa and the USA. The first objective of this research is to assess perceptions of the value of Strategic Management on their business life and what online practices they currently employ. The second objective is to identify the modes of ICT access, awareness about possible ICT’s, influence of sharing, submitting, amending and using information, taking time away from studies, etc. The third objective is to establish some differences between the two research populations in South Africa and the USA. The majority of students indicated that they experience significant value in their study of Strategy and also significant differences between the two populations about the perceived value of the ICT activities they perform.